Cardiotocografia Anteparto e Prognóstico Perinatal em Gestações Complicadas pelo Diabete: Influência do Controle Metabólico Materno - Mascaro, Moacyr Sanches [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Costa, Roberto Antonio de Araújo [UNESP]; Maestá, Izildinha [UNESP]; Bossolan, Graziela [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2002)
Objetivo: relacionar a qualidade do controle metabólico com os resultados da cardiotocografia (CTG) anteparto e avaliar sua capacidade preditiva no prognóstico perinatal de gestações associadas ao diabete. Pacientes e Métodos: estudo retrospectivo de 125 gestantes, portadoras de diabete gestacional ou clínico, no qual se relacionou a última CTG anteparto (intervalo máximo de 48 horas) à qualidade do controle metabólico materno e aos resultados perinatais. A qualidade do controle metabólico foi definida pela média glicêmica do dia do exame (MGd) e da gestação (MG) e pelo comportamento da requisição de insulina (R/insulina). Para os resultados perinatais foram analisados os índices de Apgar de 1º e 5º minuto, a classificação peso/idade gestacional, o tempo de internação, a necessidade de cuidados de UTI e a ocorrência de óbito neonatal (ONN) precoce. A capacidade diagnóstica da CTG anteparto foi avaliada pelos índices de sensibilidade, especificidade e valor preditivo positivo e negativo. Resultados: a MGd adequada (<120 mg/dL) associou-se a 2,9% dos resultados de CTG anteparto alterados e a inadequada ( > ou = 120 mg/dL), a 26,1% (p<0,005). A MG mantida inadequada se relacionou a 13,7% de CTG anteparto alterada e a adequada, a apenas 2,7% (p<0,005). O comportamento da requisição de insulina não interferiu nos resultados da CTG anteparto. Os índices de Apgar de 1º e 5º minuto, a necessidade de cuidados de UTI e a ocorrência de ONN precoce não dependeram do último traçado da CTG anteparto. O exame diferenciou o tempo de internação dos recém-nascidos: quando normal, 46,4% tiveram alta hospitalar até o 3º dia de vida e, quando alterado, 62,5% deles ficaram internados por mais de sete dias. Conclusões: os resultados alterados da última CTG anteparto relacionaram-se com níveis inadequados de MG, diária e da gestação, e não dependeram da R/insulina. O resultado normal da CTG anteparto foi adequado para garantir a saúde neonatal. Ao contrário, os resultados alterados indicaram risco de complicações nos filhos de mães diabéticas.

Background: the antepartum nonstress test (NST) is the most commonly used test to evaluate fetal well-being in pregnancies complicated by diabetes, its results being related to the quality of maternal metabolic control and perinatal prognosis. Purpose: to relate the quality of metabolic control to the results of the NST and to evaluate its predictive capacity for the perinatal prognosis of pregnancies associated with diabetes. Patients and Methods: this is a retrospective study of 125 pregnant women with gestational or clinical diabetes in which the last NST (maximum interval of 48 h) was related to the quality of maternal metabolic control and perinatal results. Quality of metabolic control was defined by the glycemic mean on the test day (GMd), glycemic mean during pregnancy (GM), and behavior of insulin requirement (Insulin/R). For the perinatal results, the following parameters were evaluated: the 1st and 5th min Apgar scores, the gestational weight/age classification, the length of hospitalization, the use of neonatal ICU, and the occurrence of early neonatal death. Diagnostic capacity of the NST in relation to the perinatal results was evaluated by sensitivity and specificity values, positive predictive value, and negative predictive value. Results: the adequate GMd (<120 mg/dL) on the test day showed that 2.9% of the NST results were abnormal; for inadequate GM (³120 mg/dL), 26.1% (p<0.005). Maintained inadequate GM during pregnancy was related to 13.7% abnormal NST; that adequate to only 2.7% (p<0.005). Insulin requirement behavior did not interfere with the NST. The 1st and 5th min Apgar scores, use of ICU, and occurrence of neonatal death did not depend on the last NST result. This test influenced the length of newborn hospitalization: when normal, 46.4% were discharged on up to the 3rd day after birth; when abnormal, 62.5% were discharged after the 7th day of birth. Conclusions: the abnormal results of the last antepartum NST correlated with inadequate MG levels (daily and during pregnancy) and did not depend on insulin/R. Normal NST was effective to ensure neonatal health. In contrast, abnormal results were related to longer hospitalization and risk for complications in diabetic mothers newborns.
Antepartum Nonstress Test and Perinatal Prognosis in Pregnancies Complicated by Diabetes: Influence of Maternal Metabolic Control
Keywords: Cardiotocografia; Diabete melito; Prognóstico perinatal; Monitorização fetal; Óbito neonatal; Antepartum non-stress test; Diabetes; Metabolic control; Perinatal prognosis